Penerapan Model Pembelajaran Round Club untuk Meningkatkan Hasil Belajar - Ari Yanto; E Kosmayadi; Elina - (Universitas Pendidikan Indonesia (UPI), 2021)
This research aims to find out the application of the round club learning model, student learning outcomes in Social Sciences (IPS) subjects in class IV SDN Karangtumaritis I Indramayu Regency. The subjects in this study were grade IV students who numbered 25 students with research objects were round Club learning models and student learning outcomes on IPS subjects. Data collection techniques use observational data, documentation and case studies. Research procedures through 4 stages namely planning, implementation, observation, and reflection. The data analysis technique used is a qualitative and quantitative data analysis technique. The indicator of the success of the research is the completeness of individual mastery with a minimum value of 71, and classical mastery of at least 85%. The result showed that the application of the round club learning model can improve student learning outcomes in IPS subjects in class IV SDN Karangtumaritis I Indramayu Regency.